2007
DOI: 10.1002/ar.20553
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes in the Testes of Eupemphix nattereri (Anura, Leiuperidae): Histological, Stereological, and Ultrastructural Aspects

Abstract: Ectothermic vertebrates have a well-developed system of melanincontaining cells, which localize in several organs and tissues and compose an extracutaneous pigmentary system. This research aimed at characterizing histological and ultrastructural patterns of pigmented cells in the testes of the anura Eupemphix nattereri (Steindachner, 1963), including the stereological and quantitative evaluation of this cell type in the gonads. Ten adult males were collected in Nova Itapirema, Sã o Paulo, Brazil, and submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…This in turn may require special adaptations to protect sperm from oxidative stress (Almbro, Dowling & Simmons, 2011), and it has been suggested that testicular melanisation (i.e. the incorporation of pigments into the tissues of the testis) might have this function (Zieri, Taboga & De Oliveira, 2007;Galvan, Møller & Erritzøe, 2011) (although this has also been suggested to be linked to thermoregulation of spermatogenesis in a lizard that shows a striking pattern of unilateral testicular melanisation; Guillette, Weigel & Flater, 1983). A case in point is the three-spined stickleback (Gasterosteus aculeatus), where sperm are made several months before the mating season and stored in the testis (Borg, 1982;Zbinden, 2001), where the testis is strongly melanised (Mehlis et al, 2012), and where brood care and territorial defence are very energy demanding (Smith & Wootton, 2005).…”
Section: When Are Sperm Needed?mentioning
confidence: 99%
“…This in turn may require special adaptations to protect sperm from oxidative stress (Almbro, Dowling & Simmons, 2011), and it has been suggested that testicular melanisation (i.e. the incorporation of pigments into the tissues of the testis) might have this function (Zieri, Taboga & De Oliveira, 2007;Galvan, Møller & Erritzøe, 2011) (although this has also been suggested to be linked to thermoregulation of spermatogenesis in a lizard that shows a striking pattern of unilateral testicular melanisation; Guillette, Weigel & Flater, 1983). A case in point is the three-spined stickleback (Gasterosteus aculeatus), where sperm are made several months before the mating season and stored in the testis (Borg, 1982;Zbinden, 2001), where the testis is strongly melanised (Mehlis et al, 2012), and where brood care and territorial defence are very energy demanding (Smith & Wootton, 2005).…”
Section: When Are Sperm Needed?mentioning
confidence: 99%
“…Testis melanisation occurs in many animal taxa, for example in fish (Louiz et al 2009), amphibians (Zieri et al 2007), reptiles (Guillette et al 1983), birds (Galván et al 2011), and mammals (Poole and Lawton 2009). In birds, for example, testicular melanisation has been evolved in species with high rates of accumulated mitochondrial mutations and has been supposed to be an adaptive response related to the protective capacity of melanin against oxidative stress (Galván et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In several vertebrates, testes are covered by melanophores that contain melanin, such as in fish (Louiz, Ben-Attia & Ben-Hassine, 2009), amphibians (Zieri, Taboga & De Oliveira, 2007), reptiles (Guillette, Weigel & Flater, 1983), birds (Galván et al, 2011), and mammals (Poole & Lawton, 2009). Melanophores contain dark pigments, which are assumed to protect the testes from deleterious UV light as a result of their strong light absorbance (Kaidbey et al, 1979;Plonka et al, 2009) or to protect male germ cells from oxidative stress (Galván et al, 2011).…”
Section: Discussionmentioning
confidence: 99%